ESPINOZA, G. Antonio, 2013, Education and the State in Modern Peru: Primary Schooling in Lima, 1821-c. 1921, Nueva York, Palgrave Macmillan. 296 pp. - Guadalupe, César (2015)
Se reseñó el libro: Education and the State in Modern Peru: Primary Schooling in Lima, 1821-c. 1921.